2-Pyridone-based fluorophores containing 4-dialkylamino-phenyl group: Synthesis and fluorescence properties in solutions and in solid state. (January 2016) - Hagimori, Masayori; Shigemitsu, Yasuhiro; Murakami, Ryo; Yokota, Kenichirou; Nishimura, Yasuhisa; Mizuyama, Naoko; Wang, Bo-Cheng; Tai, Chen-Kuen; Wang, San-Lang; Shih, Tzenge-Lien; Wu, Kuen-Da; Huang, Zhi-Shuan; et al.
Abstract: Novel highly emissive 2-pyridone-based compounds3a, b and4a–d were synthesized by a convenient one-pot method from 4-(dialkylamino)acetophenones (1a, b ) and cyanoketene dithioacetal (2a ) or sulfonyl ketene dithioacetals (2b, c ), and their fluorescence properties were investigated. A simple structure modification of 2-pyridones significantly affected their optical properties including the emission wavelength and fluorescence intensity. All the 6-(4-dialkylamino)phenyl-2-pyridones showed positive solvatofluorochromism and intense blue-green fluorescence in nonpolar solvents such as chloroform ( Ф : 0.80–0.92) and dichloromethane ( Ф : 0.83–0.94). A hypsochromic shift of the fluorescence emission maxima and strong fluorescence in a polar solvent were observed by substituting the dimethylamino group with a diethylamino group. Introduction of a sulfonyl group disturbed the molecular planarity of compounds4a, 4b, and4d, resulting in a strong fluorescence in acetone ( Ф : 0.86–0.95) and acetonitrile ( Ф : 0.59–0.88). These results indicate that 2-pyridone-based compounds have great potential as fluorophores for various practical applications. Highlights: Novel fluorescent 6-(4-dialkylamino)phenyl-2-pyridones were synthesized by a one-pot method. All the compounds showed positive solvatofluorochromism. Intense fluorescence was observed in polar and nonpolar solvents. The sulfonyl group disturbed the molecular planarity, resulting in intense fluorescence in polar solvents.